Self-esteem and family satisfaction as predictors of life satisfaction in Peruvian highland university students - Garnique-Hinostroza, Ronald; Coaquira, Odón Helar Huanca; Mamani-Benito, Oscar; Turpo-Chaparro, Josué Edison; Castillo-Blanco, Ronald; Turpo, Samuel Phala; Esteban, Renzo Felipe Carranza (Frontiers in Education, 2024)
Objective To determine whether self-esteem and family satisfaction predict life satisfaction in university students from the Peruvian highlands. Methods A cross-sectional, predictive design study with the participation of 848 Peruvian university students of both sexes (31.7% male and 68.3% female) whose ages ranged from 17 to 41 years old (M = 20.31 and SD = 3.66). The instruments used were Rosenberg’s self-esteem scale (RSE; 2000), Olson’s family satisfaction scale (FSS; 2006) and Diener’s life satisfaction scale (SWLS; 1985). Results Show that the proposed model had a fit of χ2 (269) = 1709.6, p < 0.001, CFI = 0.957, RMSEA = 0.080, SRMR = 0.061, evidencing that positive self-esteem (β = 0.21, p < 0.001) and family satisfaction (β = 0.57, p < 0.001) significantly predict life satisfaction. Unlike negative self-esteem, which does not predict life satisfaction (β = −0.09, p = 0.003). Conclusion Self-esteem, family satisfaction, life satisfaction, university students, Peru.